New lacebugs (Hemiptera: Heteroptera: Tingidae) from Upper Cretaceous Burmese amber. (February 2019) - Guilbert, Eric; Heiss, Ernst
Abstract: From the Upper Cretaceous Burmese amber, only three genera and species of Tingidae ( Spinitingis ellenbergeri Heiss and Guilbert, 2013; Burmacader multivenosus Heiss and Guilbert, 2013; and Tingiometra burmanica Heiss et al., 2015) have been reported to date. Two new genera and species Paraphatnomacader huarongcheni gen. et sp. nov. and Tingiphatnoma bispinosa gen. et sp. nov. are described and illustrated. Their phylogenetic relationships are discussed on the basis of a cladistics analysis, leading to an emergence of the Tingidae likely much older than ca. 125–135 Ma.